2019
DOI: 10.3390/toxins11090502
|View full text |Cite
|
Sign up to set email alerts
|

Genetics, Toxicity, and Distribution of Enterohemorrhagic Escherichia coli Hemolysin

Abstract: The ability to produce enterohemolysin is regarded as a potential virulence factor for enterohemorrhagic Escherichia coli (EHEC) and is frequently associated with severe human diseases such as hemorrhagic colitis (HC) and the hemolytic uremic syndrome (HUS). The responsible toxin, which has also been termed EHEC-hemolysin (EHEC-Hly, syn. Ehx), belongs to the Repeats in Toxin (RTX)-family of pore-forming cytolysins and is characterized by the formation of incomplete turbid lysis zones on blood agar plates conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 61 publications
1
33
0
Order By: Relevance
“…Intimin, encoded by the eaeA gene, adheres to intestinal mucosa and causes intestinal lesion formation [47]. Enterohemolysin, encoded by hlyA, leads to erythrocyte lysis, which may contribute to iron intake by intestinal bacteria [48]. Previous reports showed that E. coli O157:H7/Hstrains isolated from the feces of slaughtered ruminants exhibited stx2 gene prominence over the stx1 gene [34,49,50].…”
Section: Discussionmentioning
confidence: 99%
“…Intimin, encoded by the eaeA gene, adheres to intestinal mucosa and causes intestinal lesion formation [47]. Enterohemolysin, encoded by hlyA, leads to erythrocyte lysis, which may contribute to iron intake by intestinal bacteria [48]. Previous reports showed that E. coli O157:H7/Hstrains isolated from the feces of slaughtered ruminants exhibited stx2 gene prominence over the stx1 gene [34,49,50].…”
Section: Discussionmentioning
confidence: 99%
“…LtxA (trade name Leukothera ® ) may provide therapeutic applications for the treatment of hematological malignancies and immune-mediated diseases [18]. All of the mentioned cytolysins form cation-selective pores in the cell membranes as the primary event [16][17][18]20,21,24,25]. This means that antibodies directed against specific RTX toxins could protect from diseases [21].…”
mentioning
confidence: 99%
“…This means that antibodies directed against specific RTX toxins could protect from diseases [21]. RTX toxins could, therefore, serve as antigens for vaccine research and development to treat the corresponding bacterial diseases [20][21][22]. These considerations are important for diagnostic applications in human and veterinary medicine, as outlined in three contributions in this Special Issue [18,21,22].…”
mentioning
confidence: 99%
See 2 more Smart Citations